2020
DOI: 10.1177/0284185120926897
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menstrual status and pathological type on the apparent diffusion coefficient in cervical cancer: a primary study

Abstract: Background Apparent diffusion coefficient (ADC) value is an important quantitative parameter in the research of cervical cancer, affected by some factors. Purpose To investigate the effect of pathological type and menstrual status on the ADC value of cervical cancer. Material and Methods A total of 352 individuals with pathologically confirmed cervical cancer between January 2015 to December 2017 were retrospectively enrolled in this study, including 317 cases with squamous cell carcinomas (SCC) and 35 cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Notably, ADC mean values for cervical cancer according to pathological type, histological grade, depth of stromal infiltration, tumor diameter, lymphovascular invasion, and pelvic lymph node metastasis were significantly different (P<0.05) and clinicopathological characteristics were closely associated with staging and prognosis, with important clinical implications. While earlier reports have supported the predictive value of ADC mean of cervical cancer in pathological type and histological grade (19)(20)(21), consistent with our conclusions, this information was not considered the most valuable for preoperative cervical cancer patients with available tissue pathology. Our experiments showed that depth of stromal infiltration, tumor diameter, lymphovascular invasion, and pelvic lymph node metastasis evaluation with DWI is superior to MRI, and ADC mean values of these pathological factors provide important predictive parameters that can be effectively used to assess the need for postoperative supplementary radiotherapy or chemotherapy, which has important clinical implications.…”
Section: Discussionsupporting
confidence: 82%
“…Notably, ADC mean values for cervical cancer according to pathological type, histological grade, depth of stromal infiltration, tumor diameter, lymphovascular invasion, and pelvic lymph node metastasis were significantly different (P<0.05) and clinicopathological characteristics were closely associated with staging and prognosis, with important clinical implications. While earlier reports have supported the predictive value of ADC mean of cervical cancer in pathological type and histological grade (19)(20)(21), consistent with our conclusions, this information was not considered the most valuable for preoperative cervical cancer patients with available tissue pathology. Our experiments showed that depth of stromal infiltration, tumor diameter, lymphovascular invasion, and pelvic lymph node metastasis evaluation with DWI is superior to MRI, and ADC mean values of these pathological factors provide important predictive parameters that can be effectively used to assess the need for postoperative supplementary radiotherapy or chemotherapy, which has important clinical implications.…”
Section: Discussionsupporting
confidence: 82%
“…Given that previous studies suggested the age and menopausal status of patients were also independent factors in predicting the stage of CC [33][34][35], these two clinical factors were incorporated into the clinical-radiomics model. Finally, the clinical-radiomics model containing the rad-score, age, and menopausal status was established to predict the stage in patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study revealed that there was significant difference for progression-free survival between patients with squamous cell carcinoma and those with adenocarcinoma/others [ 10 ]. Moreover, the ADC values of the cervical cancers were different in different pathological types [ 17 ]. The purpose of this study was to investigate the effect of NAT + RH and CCRT on the prognosis of patients with stage IB2 and IIA2 squamous cervical cancer (SCC), and the value of ADC in outcome evaluation of different treatment strategies in the patients with IB2 and IIA2 SCC.…”
Section: Introductionmentioning
confidence: 99%